Postviral asthenia and fatigue syndrome in a therapist's practice - V I Simanenkov; E G Poroshina; V V Makienko (Терапевтический архив, 2012)
Asthenia serves as a symptom of many both organic and mental diseases. 16-64% of patients with this diagnosis visit a polyclinic therapist. Asthenia is an obligate symptom of a number of mental illnesses, including stress-related neurotic disorders, and somatoform disorders (panic attacks, generalized anxiety disorders, somatoform autonomic disorders, adjustment disorders), as well as nonpsychotic petit mal depressions. Patients with these disorders generally see therapists or general practitioners, rather than psychiatrists. The paper reflects the classification, differential diagnosis, and treatment of asthenia. A clinical case is described; its therapy is warranted.